Legal Proceedings in Digital Rights in Independent Procedural System - V. A. Mayboroda; E. T. Mayboroda (Теоретическая и прикладная юриспруденция)
Digital rights are an object of civil circulation that has a number of specific features. Such features, in particular, include: the ability to use only through software and hardware, circulation within the framework of an information system and not the material world, self-verification of belonging to a specific subject. Therefore, disputes about digital rights have at least three specific features: these are the disputes about economic assets; the relevant evidence is contained in the very subject of the dispute; these are disputes about a right that does not have property, that is, with the possibility of applying the law following the subject, and not the law at the location of the property.The purpose of the study is to understand the peculiarities of the circulation of digital rights as objects of civil law regulation and to identify the possibilities for the specific consideration of disputes, the subject of which are digital rights.Research methods: teleological, comparative and content analysis of law enforcement. Using the teleological method, the intended purpose of regulating the circulation of digital rights was identified. The comparative analysis in the article made it possible to put forward and motivate the opinion on the need to create a specialized court to resolve disputes, the subject of which is digital rights. A limited content analysis of law enforcement practice made it possible to identify the current features of substantive resolution of disputes related to digital rights.The conclusions of the study are based on the postulate that the legal force of a judicial act resolving a dispute on the merits in relation to a certain digital right will make it possible to determine not only the further legal fate of digital law as an economic asset, but also to authorize the circulation of digital law, to stop (prohibit) the circulation of digital rights or prescribe significant conditions for the circulation of digital rights.